2017
DOI: 10.1111/jzo.12527
|View full text |Cite
|
Sign up to set email alerts
|

Steep converse Bergmann's cline in a carrion beetle: between‐ and within‐population variation in body size along an elevational gradient

Abstract: Body size is an integrative trait with substantial fitness consequences in animals. Geographical clines in body size have fascinated biologists because of their potential to provide insight into the mechanisms governing local adaptation and phenotypic plasticity. In this complex study, we focused on variation in body size of Silpha carinata (Coleoptera: Silphidae) along elevation gradients in Central Europe. Altitudinal clines were investigated separately for males and females as sex-specific responses to envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 66 publications
0
5
1
Order By: Relevance
“…Usually, researchers study body size variation in insects for both genders. They note decreasing or increasing body size in high elevation [47,48,49]. Our results in SSD variation differ from those of other researchers.…”
Section: Discussioncontrasting
confidence: 99%
“…Usually, researchers study body size variation in insects for both genders. They note decreasing or increasing body size in high elevation [47,48,49]. Our results in SSD variation differ from those of other researchers.…”
Section: Discussioncontrasting
confidence: 99%
“…Apart from those using T‐statistics, only a few studies have dealt with changes in trait distribution (of which variance is the simplest metric) with elevation (e.g., Baranovská & Knapp, 2018; Classen et al., 2017). In general, studies have reported increased variability in traits under “favorable conditions” at lower elevations where intra‐ and interspecific competition drives trait divergence (Ding et al., 2019; Mayfield & Levine, 2010), while habitat filtering due to extreme environmental conditions at higher elevations is associated with reduced trait variance (de Bello et al., 2009; Kraft & Ackerly, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The wing shape and size of E. cordata seems to be traits that vary between habitats, which may explain the presence of correlation found among these variables with phytophysiognomy type, latitude, longitude and altitude. These morphometric variations observed may be related to different populations responses to the local environmental characteristics of each phytophysiognomy, because insects may have plastic morphological adaptations in response to altitudinal and latitudinal geographical gradients (Baranovská & Knapp, 2018), or to local variations in landscape elements (Ribeiro et al, 2019). Grassi-Sella et al (2018) found a pattern of morphometric clustering in E. annectans and E. truncata related to the phytophysiognomy from which the populations were sampled, being such pattern attributed to phenotypic plasticity.…”
Section: Discussionmentioning
confidence: 99%